2018
DOI: 10.3390/ani8090151
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Perceptual Differences between Sexes in Dogs: An Overview

Abstract: Simple SummaryWe explore the differences in male and female dogs regarding personality traits as well as cognitive and perceptual processes. Our aim was to explore whether the differences in male and female dogs were affected by the domestication process. The results show that dogs are largely in line with the life-history theories, reflecting the sex differences described in wild animals.AbstractIn this paper, we review the scientific reports of sex-related differences in dogs as compared to the outcomes desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 218 publications
(298 reference statements)
7
35
1
Order By: Relevance
“…Differences in boldness and shyness are acknowledged predictors of performance in working dogs, with bolder animals being the better performers [ 42 ]. Boldness is an individual characteristic providing less aversion to risk or novelty that enables the individual actively seeking out and engaging in social cooperative and competitive interactions [ 43 ]. This mirrors the recently reported opinions of working farm dog handlers, who identified boldness in their dogs as a desirable trait.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in boldness and shyness are acknowledged predictors of performance in working dogs, with bolder animals being the better performers [ 42 ]. Boldness is an individual characteristic providing less aversion to risk or novelty that enables the individual actively seeking out and engaging in social cooperative and competitive interactions [ 43 ]. This mirrors the recently reported opinions of working farm dog handlers, who identified boldness in their dogs as a desirable trait.…”
Section: Discussionmentioning
confidence: 99%
“…However, female to male ratio inverted in CB, which suggests a certain interest for breeders and owners in the males of the CB breed, which could be presumably linked to their application as guard or shepherding animals. In nature, for males, territorial defense versus access to female success ratio may be balanced by ameliorative reproductive success, whereas females have fewer direct advantages from this ratio; hence, the energy invested in the defense may be detracted by the functions related to the sex-specific behaviors linked to reproduction [ 43 ]. The same authors suggested that male dogs tend to be more social and to engage more in dog/human contact than females, whereas, in cooperative behavior in trying to solve a problem, the opposite trend has been found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, more males were reported for episodes of aggression compared to females. This aspect has been demonstrated in several studies, and it might be explained by the tendency of males to be more competitive and more prone to use confrontation rather than appeasement in social conflict [26,27]. A significant difference in gender distribution was found between the group of dogs aggressive towards humans and the group of dogs aggressive towards other dogs, with a higher number of entire and spayed females in the latter group.…”
Section: Discussionmentioning
confidence: 67%
“…This could be related to the fact that dominant females were more often neutered than dominant males. Previous studies have determined that hormonal activity influences inter-dog aggression (Sherman et al, 1996) and aggression has been found to be more frequent in neutered females compared to intact females and neutered males (Wright & Nesselrote, 1987, Scandurra et al, 2018. Our study has several limitations: (1) We did not measure the dominant behaviour of the dogs, only the dominance perceived by the owner.…”
Section: Discussionmentioning
confidence: 95%